Mastering your fellowship: Part 1, 2024 - Klaus B. von Pressentin; Mergan Naidoo; Frederick Mayanja; Selvandran C. Rangiah; Ramprakash Kaswa (South African Family Practice, 2024)
The series, ‘Mastering your Fellowship’, provides examples of the question formats encountered in the written and clinical examinations, Part A of the Fellowship of the College of Family Physicians (South Africa) (FCFP [SA]) examination. The series is aimed at helping family medicine registrars (and their supervisors) in preparing for this examination.